Strain behavior of lanthanum modified BiFeO3 thin films prepared via soft chemical method - Simões, Alexandre Zirpoli [UNESP]; Aguiar, E. C. [UNESP]; Gonzalez, A. H. M. [UNESP]; Andres, J.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2008)
Pure and lanthanum modified BFO (LaxBi1-xFeO3, x=0.0, 0.08, 0.15, 0.30) thin films were fabricated on Pt(111)/Ti/SiO2/Si substrates by the soft chemical method. The effect of La substitution on the structural and electrical properties was studied. Scanning electron microscopy, x-ray diffraction, and Raman spectroscopy have been employed to characterize the thin films while the piezoelectric measurements were carried out using a setup based on an atomic force microscope. It was found that La-doped BFO thin films exhibited good ferroelectric properties, such as improved leakage current density and retention-free characteristics. The unipolar strain is strongly reduced by the amount of lanthanum added to the system.
Keywords: annealing; antiferromagnetic materials; atomic force microscopy; bismuth compounds; dielectric polarisation; ferroelectric switching; ferroelectric thin films; lanthanum compounds; leakage currents; multiferroics; piezoelectricity; platinum; Raman spectra; scanning electron microscopy; silicon; silicon compounds; titanium; X-ray diffraction